Myositis Associated with the Anti-COVID-19 Covishield Vaccine - Miqdadi, Amal; Benmansour, Nouhad; Herrag, Mohammed (Current Respiratory Medicine Reviews, 2023)
Introduction: The SARS-CoV-2 made the world stop its activities, and the only chance of returning to normal life is the vaccine. But like any vaccination, some complications have been reported. We report the case of a patient who presented a myositis following the administration of the Covishield* (AZD1222, ChAdOx1 nCoV-19, AstraZeneca) COVID-19 vaccine. Case Report: 12 hours after his first dose, an 84-year-old patient presented to us reporting a decreased muscle strength: the patient can move against gravity but not against resistance. The biological assessment showed that CK was at 4,250 IU/L, myoglobin was at 144 microgram/L and aldolases at 16.9 U/L. The patient received high doses of corticosteroids. Discussion: The development of vaccines and immunization programs reduced the morbidity and mortality of several diseases. Other case reports suggested the possible association between myopathies and the administration of the hepatitis B vaccine and H1N1 plus the seasonal trivalent influenza and other vaccines. The exact mechanism is still unknown, but a presumable autoimmune phenomenon is incriminated. Conclusion: The main purpose of this case report is to raise awareness about the possible link between the COVID-19 vaccination and polymyositis and the urge to take charge to avoid further complications.
Keywords: AZD1222